How political regime and trade liberalization help to rethink development in Central Africa: empirical evidence - Tchouassi, Gérard (Ciência & Trópico, 2013)
ABSTRACT Can political regime and trade liberalization help to re-think development? This paper has documented the strong presumption that political regime and trade liberalization contribute positively to economic development. The main objective of this research is to estimate econometrically the impact of political regime on trade flows in order to channelize economic development in Central Africa countries. A panel of Central Africa countries has been used to test empirically the predictions. The empirical evidences show that there is a correlation between human development indicators, inflation, importations and exportations. Imports and democracy have a positive effect on the level of development in Central Africa countries. Findings show that the capacity building programme on “good governance agenda”, fostered by many international institutions, is an important initiative to be used to counterbalance the negative impact that varieties of democracy systems have on economic development. KEYWORDS: Political regime. Democracy. Trade liberalization. Development. Central Africa. Como os regimes políticos e a liberalização do comércio ajudam a repensar o desenvolvimento na África Central: uma evidência empíricaRESUMO O regime político e a liberalização do comércio podem ajudar a repensar o desenvolvimento? Este trabalho tem documentado a forte presunção de que o regime político e a liberalização do comércio contribuem positivamente para o desenvolvimento econômico. O objetivo principal da pesquisa é estimar econometricamente o impacto do regime político sobre os fluxos comerciais, a fim de canalizar o desenvolvimento econômico em países da África Central. Um painel de países da África Central tem sido utilizado para testar empiricamente as previsões. As evidências empíricas mostram que há uma correlação entre os indicadores de desenvolvimento humano, inflações, importações e exportações, em que as importações e a democracia têm um efeito positivo sobre o nível de desenvolvimento dos países da África Central. Os resultados mostram que o programa de capacitação na «agenda da boa administração», promovida por muitas instituições internacionais, é uma iniciativa importante para ser utilizada para contrabalançar o impacto negativo que as variedades de sistemas de democracia têm no desenvolvimento econômico. PALAVRAS-CHAVE: Regime político. Democracia. Liberalização do comércio. Desenvolvimento. Bem-estar. Integração regional. África Central.